TRANSLATION-ORIENTED TERMINOLOGY IN UKRAINE:EMERGENCE, FUNDAMENTALS AND PROSPETS - САЙКО, Михайло (Київський національний університет імені Тараса Шевченка, Навчально-науковий інститут філології, 2023)
The article focuses on the development of translation-oriented terminology as a separate convergent field of philological science in Ukraine, the actual date of which can rightly be considered 2020. It is stated that the impetus for its emergence was the limited reproductive (technique/transformational) approach of classical translation studies to the investigation of specialized translation. In addition to its object, subject and a number of tasks, the article identifies five conceptual positions of translation-oriented terminology, which significantly change the view on language and translation. Specifically, it posits that the main function of language and translation is creation rather than communication, whereas translation itself is a third-order simulacrum or hyperreality. Taking into account that the order cannot be born out of chaos, a creator, who relies on empirically verified language principles and laws, but not the observed facts, is an especially relevant figure in the field. The author distinguishes between translational, lexicographic, standard-related and situational areas of translation-oriented terminology research. The article provides a helpful list of resources for potential research in the German-Ukrainian direction, which could facilitate proper multidomain terminology regulation and standardization efforts. Based on the current needs of science and society, including the translation market, the outlined perspectives and tasks of translation-oriented terminology confirm its relevance and importance. It is noteworthy that translation- oriented terminology offers a significant advantage compared to other fields due to the applicability of its findings and standardization achievements, which initially address national priorities and ensure the provision of high-quality specialized translations.

Присвячено питанням розвою перекладового термінознавства як окремого конвергованого напряму філологічної науки в Україні. Констатовано, що за підґрунтя для його виникнення правив обмежений відтвірний (або ж способово-трансформаційний) підхід класичного перекладознавства до вивчання галузевого перекладу. Окрім об'єкта, предмета та низки завдань перекладового термінознавства, у статті визначено п'ять його концепційних позицій, що значно змінюють погляд не лише на мову, одначе й на переклад. Вирізнено власне перекладову, лексикографічну, стандартову та ситуативну площини перекладово- термінознавчих розвідок. Надано дороговказовий перелік матеріялів для потенційних розвідок у німецько-українському напрямі задля належного внормування та стандартування різногалузевої термінології. Окреслені перспективи перекладового термінознавства лише підтверджують його релевантність серед инших галузей. _____________ СПИСОК ВИКОРИСТАНИХ ДЖЕРЕЛ Дорофеєва М. С., Сайко М. А. Категорія роду німецьких та українських медичних термінів крізь призму перекладового термінознавства. Мова і культура. Київ, Вип. 22. Т. V (200). С. 314-319. Іващенко В. Л., Яценко Н. О. Українське перекладне терміно- знавство на тлі слов'янського досвіду. Науковий вісник Чернівецького університету. Сер. : Германська філологія. Вип. 692-693. С. 39-44. Сайко М. А. Відтворювання і стандартизація медичної термінології в німецько-українських лексикографічних джерелах : дис. ... доктора філософії. : 035. Київ, 2021. 276 с. Сайко М. А. Німецько-український медичний словник. Із поясненнями та прикладами терміновживання. Понад 18 000 словникових статей. К : ВД "Освіта України", 2021. 348 с. Сайко М. А. Переклад як симулякр та симулякри в перекладі. Закарпатські філологічні студії. Вип. 9. Т. 2. С. 64-69. Сайко М. А. Словотвірні симулякри в медичній термінології. Закарпатські філологічні студії. Вип. 10. Т. 2. С. 59-64. Сайко М. А. Стандартизація медичної термінології крізь призму перекладового термінознавства. Innovation in science: modern challenges : The 3rd international scientific and practical conference, Munich, May 25-26, 2020. Littera Verlag : Munich, 2020. Pp. 234-237. Хацер Г. О. Особливості перекладу термінологічної лексики на прикладі текстів медичного спрямування. Наукові записки Ніжинського державного університету ім. Миколи Гоголя. Сер. : Філологічні науки. Кн. 3. С. 151-154. Яценко Н. Перекладне термінознавство в Україні кінця XX - початку XXI ст. Українська мова. 2012, № 3. С. 94-110. Bowker L. Terminology and Translation. Handbook of Terminology. Amsterdam; Philadelphia : John Benjamins, V. 1. P. 303-323. Buhler H. Translation(swissenschaft) und Terminologie (wissenschaft) im akademischen Facherkanon. Versuch einer Klarung. Fluctuat nec mergitur. Translation und Gesellschaft : Forum Transaltionswissenschaft. Frankfurt am Main, 2005. B. 4. S. 72-82. Galinski Ch., Budin G. New trends in translation-oriented terminology management. Scientific and technical translation. Amsterdam, 1993. Vol. VI. P. 209-216. Murath J. Translation-oriented terminology work in Hungary. Terminology in Everyday Life / ed. by M. Thelen, F. Steurs. Amsterdam; Philadelphia : John Benjamins, 2010. Pp. 47-60. Sierra Ch. V. Translation-oriented terminology management and ICTs: present and future. Interdisciplinarity and languages : Current Issues in Research, Teaching, Professional Applications and ICT. Bern, 2011. Pp. 45-64. Snell-Hornby M., Budin G. Translationswissenschaft in Wien - Zur Pionierrolle einer altehrwurdigen Universitat. Reflexive Innensichten aus der Universitat. Disziplinengeschichten zwischen Wissenschaft, Gesellschaft und Politik. Gottingen : V & R unipress; Vienna University Press, 2015. S. 239-252. Thelen M. Relations between terms: a cognitive approach. The interaction between terminology, lexicology, translation studies and translation practice. Linguistica Antverpiensia. New series : themes in translation studies. 1. Pp. 193-209. Thelen M. The interaction between terminology and translation or where terminology and translation meet. Trans-com. 8(2). Pp. 347-381.
ПЕРЕКЛАДОВЕ ТЕРМІНОЗНАВСТВО В УКРАЇНІ: СТАНОВЛЕННЯ, ОСНОВИ ТА ПЕРСПЕКТИВИ
Keywords: перекладознавство; термінознавство; перекладове термінознавство; галузевий переклад; галузева лексикографія; стан- дартування термінології; translation studies; terminology science; translation-oriented terminology; specialized translation; specialized lexicography; terminology standardization